Study on deformation control of overlying strata in short-wall coordinated filling mining of thick coal seam under aquifer - Yao, Yinan; Jiang, Pengfei; Zhou, Nan; Du, Erbao (Frontiers in Earth Science, 2023)
The mining of coal resources and the protection of water resources are often in opposition, and this contradiction is more prominent in the mining of thick coal seams due to the difficulty of controlling the overburden deformation. Based on the mining conditions of thick coal seam under the main aquifer of a coal mine in the water shortage area of Northwest China, this paper puts forward the short-wall coordinated filling mining (SCFM) of thick coal seam. The stress analysis of the overall structure consisting of the top and bottom plates, coal pillars and filler at each stage of the mining process was carried out, the length of the short-walled working face suitable for this coal mine was derived, and the key parameters for the mining of the three pan areas of the mine were designed. The analysis results show that the sensitivity of the maximum tensile stress in the roof to the length of the working face is better than the filling rate in the case of short-walled working face arrangement. When the design coal mine working face length is 40m and the filling rate is 95%, the overburden fissure development height can be controlled to 58.45m after the whole area of three pan area is retrieved. It is verified by the downhole injection method that the requirement of non-conducting aquifer is satisfied after using SCFM. The research in this paper is of great significance to achieve safe and efficient recovery of coal resources and water conservation under strongly water-rich rock formations.